Flares and habitability - Abrevaya, X.C. (2011)
At present, dwarf M stars are being considered as potential hosts for habitable planets. However, an important fraction of these stars are flare stars, which among other kind of radiation, emit large amounts of UV radiation during flares, and it is unknown how this events can affect life, since biological systems are particularly vulnerable to UV. In this work we evaluate a well known dMe star, EV Lacertae (GJ 873) as a potential host for the emergence and evolution of life, focusing on the effects of the UV emission associated with flare activity. Since UV-C is particularly harmful for living organisms, we studied the effect of UV-C radiation on halophile archaea cultures. The halophile archaea or haloarchaea are extremophile microorganisms, which inhabit in hypersaline environments and which show several mechanisms to cope with UV radiation since they are naturally exposed to intense solar UV radiation on Earth. To select the irradiance to be tested, we considered a moderate flare on this star. We obtained the mean value for the UV-C irradiance integrating the IUE spectrum in the impulsive phase, and considering a hypothetical planet in the center of the liquid water habitability zone. To select the irradiation times we took the most frequent duration of flares on this star which is from 9 to 27 minutes. Our results show that even after considerable UV damage, the haloarchaeal cells survive at the tested doses, showing that this kind of life could survive in a relatively hostile UV environment. © 2012 International Astronomical Union.